2018
DOI: 10.1111/bph.14333
|View full text |Cite
|
Sign up to set email alerts
|

Novel inhibitors of the cellular renin‐angiotensin system components, poricoic acids, target Smad3 phosphorylation and Wnt/β‐catenin pathway against renal fibrosis

Abstract: The secolanostane tetracyclic triterpenoids effectively blocked RAS by simultaneously targeting multiple RAS components and lanostane tetracyclic triterpenoids inhibited renin and protected against tubulo-interstitial fibrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
91
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 149 publications
(93 citation statements)
references
References 61 publications
2
91
0
Order By: Relevance
“…TCM gain increasingly more attention all over the world, based on their specific futures and long historical clinical practice . Metabolomics afforded a research idea that is similar to the overall concept of TCM .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TCM gain increasingly more attention all over the world, based on their specific futures and long historical clinical practice . Metabolomics afforded a research idea that is similar to the overall concept of TCM .…”
Section: Discussionmentioning
confidence: 99%
“…TCM gain increasingly more attention all over the world, based on their specific futures and long historical clinical practice. [30][31][32][33][34][35] Metabolomics afforded a research idea that is similar to the overall concept of TCM. [36] Metabolomics technique has been extensively applied to the study of TCM and natural products.…”
Section: Discussionmentioning
confidence: 99%
“…We report for the first time that petA, a novel small molecule ex- The antifibrotic actions of petA may involve multiple mechanisms. Because TGF-β1/Smad3 signalling is the critical pathway of renal fibrosis, 3,4,[36][37][38] we first examined the effect of petA on the activation of TGF-β1/Smad3 signalling in the UUO model. Our results indicated that administering petA to prevent or treat UUO suppressed TGF-β1 expression and blocked the phosphorylation of Smad3, subsequently attenuating the expression of fibrotic genes (including α-SMA, collagen I and fibronectin).…”
Section: Discussionmentioning
confidence: 99%
“…[151][152][153][154][155][156][157][158] Recently, our group isolated more than 90 triterpenoid compounds from the surface layer of Poria cocos, some of which exhibited significant antifibrotic properties. [159][160][161] New triterpenoids, including poricoic acid ZC, poricoic acid ZD, and poricoic acid ZE, significantly downregulated the expression of Wnt1, active β-catenin, Snail, Twist, MMP-7, PAI-1, and FSP1 in HK-2 cells induced by TGF-β1 and angiotensin II and mice with unilateral ureteral occlusion 29 (Figure 2 and Table 1). Moreover, new triterpenoids, including poricoic acid ZG and poricoic acid ZH, improved renal fibrosis by targeting the phosphorylation of Smad3 signaling and the Wnt/β-catenin signaling pathway 162 (Figure 2 and Table 1).…”
Section: Wnt Signaling Pathwaymentioning
confidence: 96%